2015
DOI: 10.1039/c5nr00706b
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome-controlled efficient ROS overproduction against cancer cells with a high pH-responsive catalytic nanosystem

Abstract: Excess reactive oxygen species (ROS) have been proved to damage cancer cells efficiently. ROS overproduction is thus greatly desirable for cancer therapy. To date, ROS production is generally uncontrollable and outside cells, which always bring severe side-effects in the vasculature. Since most ROS share a very short half-life and primarily react close to their site of formation, it would be more efficient if excess ROS are controllably produced inside cancer cells. Herein, we report an efficient lysosome-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 49 publications
0
49
0
Order By: Relevance
“…Oxidatively sensitive non-fluorescence probe DCFH-DA was utilized to measure the intracellular ROS level. DCFH-DA can be deacetylated by nonspecific esterase to form DCFH, which was further oxidized by intracellular ROS to produce a stable fluorescent ROS-sensitive compound 2 ′, 7 ′-dichlorofluorescein (DCF) [ 36 ]. In this study, 4T1 cells were seeded into petri dishes at a density of 5.0 × 10 4 cells and cultured with serum-free media containing FPO@HMSNs-PAA (16 and 32 μg·mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Oxidatively sensitive non-fluorescence probe DCFH-DA was utilized to measure the intracellular ROS level. DCFH-DA can be deacetylated by nonspecific esterase to form DCFH, which was further oxidized by intracellular ROS to produce a stable fluorescent ROS-sensitive compound 2 ′, 7 ′-dichlorofluorescein (DCF) [ 36 ]. In this study, 4T1 cells were seeded into petri dishes at a density of 5.0 × 10 4 cells and cultured with serum-free media containing FPO@HMSNs-PAA (16 and 32 μg·mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…These results confirmed that the pretreatment of primary neuron cells with AuNCs‐NH 2 exhibited excellent protection from the H 2 O 2 ‐induced toxicity. It should be noted that IONPs and Ac‐G 9 PtNPs have been reported to enhance H 2 O 2 ‐induced cell damage dramatically due to their intrinsic peroxidase‐like activity under H 2 O 2 challenge . In contrast, neurons treated with AuNCs‐NH 2 did not enhance cell death after H 2 O 2 challenge, supporting that the peroxidase‐like activity of AuNCs‐NH 2 was negligibly weak intracellularly.…”
Section: Resultsmentioning
confidence: 88%
“…The fluorescence intensity of this derivative correlates with the level of ˙OH radical formation. 68 The preparation of NaTA was carried out by neutralization of 0.8 g of TA with 50 mL of aqueous 0.05 N NaOH solution with constant stirring for 1 h. Then, 8.3 g of NaOH were added to reach 14% by weight concentration and favor the precipitation of the desired product. Under these conditions, the precipitate NaTA was filtered and dried in an oven at 110 °C for 12 hours.…”
Section: Methodsmentioning
confidence: 99%